2017
DOI: 10.1038/s41467-017-00506-7
|View full text |Cite
|
Sign up to set email alerts
|

A gateway towards non-collinear spin processing using three-atom magnets with strong substrate coupling

Abstract: A cluster of a few magnetic atoms on the surface of a nonmagnetic substrate is one suitable realization of a bit for spin-based information technology. The prevalent approach to achieve magnetic stability is decoupling the cluster spin from substrate conduction electrons in order to suppress destabilizing spin-flips. However, this route entails less flexibility in tailoring the coupling between the bits needed for spin-processing. Here, we use a spin-resolved scanning tunneling microscope to write, read, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 51 publications
(94 reference statements)
1
51
0
2
Order By: Relevance
“…This play-ground is particularly attractive given that several STM experiments have reported clear observations of stable magnetic moments in this type of composite system (see e.g., Refs. [112,63,113]). This strongly suggests that local fluctuation effects decrease with increasing cluster size, a feature that is in qualitative accordance with one main finding presented throughout the review, namely that the relative impact of the fluctuations becomes smaller the larger the magnetic moment gets.…”
Section: Discussionmentioning
confidence: 99%
“…This play-ground is particularly attractive given that several STM experiments have reported clear observations of stable magnetic moments in this type of composite system (see e.g., Refs. [112,63,113]). This strongly suggests that local fluctuation effects decrease with increasing cluster size, a feature that is in qualitative accordance with one main finding presented throughout the review, namely that the relative impact of the fluctuations becomes smaller the larger the magnetic moment gets.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [15]. The cleaned Pt(111) surface was coated with a fraction of a monolayer Co resulting in monolayer islands and stripes (see Supplementary Note 1) before single Fe atoms were deposited on the pre-cooled sample leading to a statistical distribution of Fe atoms on the Pt terraces.…”
Section: Methodsmentioning
confidence: 99%
“…This surprising finding was rationalized in terms of an Dzyaloshinskii-Moriya-enhanced Ruderman-Kittel-Kasuya-Yosida (RKKY) interaction. 14 These earlier results obtained on MnO 2 /Ir(001) showed that this indirect magnetic coupling mechanism which was previously only observed for assemblies of single atoms or clusters on Pt(111) surfaces 15,16 can also result in chiral magnetic order in laterally extended structures.…”
Section: Introductionmentioning
confidence: 85%